Kontribusi Korea Selatan Dalam Pemulihan Ekonomi Indonesia Pasca Pandemi - Alfikri Oktavian Yudhistira; Arie Kusuma Paksi (Mahesa Research Center, 2022)
The Covid-19 pandemic, which has now become a global challenge, has implications for all sectors of life, especially the economic sector. Indonesia is one of the countries whose economy has been affected by this pandemic situation. One of the policies that must be taken by the Indonesian government is to initiate the National Economic Recovery program. This study aims to analyze the contribution made by South Korea to Indonesia which has a cooperative relationship between the two countries in Indonesia's economic recovery after the pandemic. The data in this study were collected through a descriptive technique of study analysis or literature review with a focus on international cooperation relations between Indonesia and South Korea during the Covid-19 pandemic and analyzed qualitatively using secondary data. The results showed that South Korea contributed to Indonesia's economic recovery after the pandemic through cooperation in various sectors such as investment, export-import and trade, energy and mineral resources, tourism to e-commerce through K-Pop. In contrast to previous studies, this study concludes that the cooperation between the two countries has brought significant results in Indonesia's economic recovery after the pandemic.